Community perception and environmental effects of flood mitigation plans in Segamat, Johor - Ramli, Muhammad Wafiy Adli; Alias, Nor Eliza; Yusop, Zulkfli (GADING Journal for the Social Sciences, 2025)
After severe floods in Segamat in 2006 and 2011, the government initiated a flood mitigation plan for the Segamat River, completed in 2015. However, in early 2017, Segamat experienced flooding again, raising questions about the project's effectiveness. This study focuses on Mukim Gemereh, located near the Segamat River. The study examined the flood history in the area, targeting three frequently flooded villages: Kampung Batu Badak, Kampung Gemereh 3, and Kampung Lubuk Batu. Findings reveal a mixed perception, with many acknowledging reduced floods impact but expressing concerns over the disrupted river ecosystem and declining fish and shrimp populations. Fishermen reported significant negative impacts on their income due to decreased catches. Most respondents are people who have experience floods before. Seventy per cent of respondents were satisfied with the flood mitigation project has been done and felt the project successful in reducing the impact of floods. However, for fisherman, the constructed flood mitigation project has affected their income as the project disturbs the habitat inside the river. The study underscores the importance of involving local communities in disaster risk management to enhance disaster management practices, as highlighted by the Sendai Framework 2015-2030. Overall, there are positive impacts, particularly regarding reduced flood risk and property damage. However, issues such as disturbed river ecosystems and stagnant water remain.